Service and service systems : provider challenges and directions in unsettled times - Baron, Steve (J. Steve); Hunter-Jones, Philippa; Warnaby, Gary. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
Unsettled times can arise from a variety of causes, including environmental (e.g., earthquake), climatic (e.g., floods), economic (e.g., recession), social (e.g., illness), or political (e.g., civil unrest). They can result in citizens' loss of homes/possessions, jobs, health, or mobility. Citizens move from above the level of consumption adequacy, where their behaviors reflect long-term and higher-order needs, to below the level of consumption adequacy, where they are forced into a short-term focus on simple existence. In parallel, (service) organizations--utilities, transport, medical, cleaning, housing, education, broadcasting, national and local government-- may become ineffective or unavailable: in other words, beyond the means of a significant proportion of citizens. This book explores the effect of unsettled times on spatial service systems. It provides original insights for managers of service organizations (especially public services), policy makers, and service system researchers and students.
1. Living in unsettled times -- 2. Schools of thought -- 3. Consumption adequacy -- 4. A service science perspective: urban service systems -- 5. Urban service systems in unsettled times -- 6. Impact, likelihood, and resilience: analyzing service system responses to unsettled times -- 7. Unsettled times: the case of the UK "big freeze" of 2010 -- 8. Bringing it altogether: purposeful proposals, challenges, and directions -- Notes -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 143-148) and index.
Title from PDF title page (viewed on January 4, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Crisis management; Emergency management; Disaster relief; Human services; unsettled times; consumption adequacy; service systems; public services; places; spatial service systems; Electronic books